The construction of knowledge in psychology: The legitimation of medicalization - Firbida, Fabíola Batista Gomes [UNESP]; Vasconcelos, Mário Sérgio [UNESP] (FapUNIFESP (SciELO), 2019)
The medicalization is an ideological process that transforms social problems into biological ones and has legitimated by Medicine and Psychology in several historical moments to hide social inequalities, placing on the individual the responsibility for its failure. In the area of Education, the number of children diagnosed with learning and medical disorders is alarming, evidencing a period called the Age of Disorders. In this article, we seek to uncover the role that relations between these two areas of knowledge historically played in the construction of the medicalization process in the Brazilian educational context.
Keywords: History of psychology; Medicalization; Psychologist training